2012
DOI: 10.1111/j.1365-2516.2011.02730.x
|View full text |Cite
|
Sign up to set email alerts
|

Correlating clinical manifestations with factor levels in rare bleeding disorders: a report from Southern India

Abstract: Data on the clinical manifestations of patients with clotting factor defects other than Haemophilia A, B and von Willebrand disease are limited because of their rarity. Due to their autosomal recessive nature of inheritance, these diseases are more common in areas where there is higher prevalence of consanguinity. There is no previous large series reported from southern India where consanguinity is common. Our aim was to analyze clinical manifestations of patients with rare bleeding disorders and correlate the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
30
0
8

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(42 citation statements)
references
References 28 publications
4
30
0
8
Order By: Relevance
“…Almost half (49.2%) of our patients with RFD were born from consanguineous marriages. Similar results have been reported from countries with similar cultural characteristics [19,20]. Our patient group represents the paediatric population, with a median age of seven at presentation.…”
Section: Discussionsupporting
confidence: 85%
“…Almost half (49.2%) of our patients with RFD were born from consanguineous marriages. Similar results have been reported from countries with similar cultural characteristics [19,20]. Our patient group represents the paediatric population, with a median age of seven at presentation.…”
Section: Discussionsupporting
confidence: 85%
“…In the study of Peyvandi et al [10] in 2012, a poor relationship was found between FV activity and clinical bleeding episodes. In another study that was performed by Viswabandya et al [12] in 2012, 33 patients with FVD were divided into two groups based on the factor's activity, i.e. patients with FV activity <1% and patients with FV activity >1%.…”
Section: Discussionmentioning
confidence: 99%
“…There is some uncertainty with respect to the cut off levels to be applied for afibrinogenemia and hypofibrinogenemia. Recent data from an Indian registry, classifies patients as having afibrinogenemia if there is no detectable clot, as hypofibrinogenemia if fibrinogen levels are less than 1 g/l and as dysfibrinogenemia if they are more than 1 g/l with other supportive tests [3]. According to the Rare Bleeding Disorder Working Group, patients with congenital afibrinogenemia have fibrinogen levels of less than 50 mg/dl.…”
Section: Discussionmentioning
confidence: 99%